MicroRNA-7 Regulates Migration and Chemoresistance in Non-Hodgkin Lymphoma Cells Through Regulation of KLF4 and YY1 - Morales-Martinez, Mario; Vega, Gabriel G.; Neri, Natividad; Nambo, M. J; Alvarado, Isabel; Cuadra, Ivonne; Duran-Padilla, M. A.; Huerta-Yepez, Sara; Vega, Mario I. (Frontiers in Oncology, 2020)
The discovery and description of the role of microRNAs has become very important, specifically due to their participation in the regulation of proteins and transcription factors involved in the development of cancer. microRNA-7 (miR-7) has been described as a negative regulator of several proteins involved in cancer, such as YY1 and KLF4. We have recently reported that YY1 and KLF4 play a role in non-Hodgkin lymphoma (NHL) and that the expression of KLF4 is regulated by YY1. Therefore, in this study we analyzed the role of miR-7 in NHL through the negative regulation of YY1 and KLF4. qRT-PCR showed that there is an inverse expression of miR-7 in relation to the expression of YY1 and KLF4 in B-NHL cell lines. The possible regulation of YY1 and KLF4 by miR-7 was analyzed using the constitutive expression or inhibition of miR-7, as well as using reporter plasmids containing the 3 'UTR region of YY1 or KLF4. The role of miR-7 in NHL, through the negative regulation of YY1 and KLF4 was determined by chemoresistance and migration assays. We corroborated our results in cell lines, in a TMA from NHL patients including DLBCL and follicular lymphoma subtypes, in where we analyzed miR-7 by ISH and YY1 and KLF4 using IHC. All tumors expressing miR-7 showed a negative correlation with YY1 and KLF4 expression. In addition, expression of miR-7 was analyzed using the GEO Database; miR-7 downregulated expression was associated with pour overall-survival. Our results show for the first time that miR-7 is implicate in the cell migration and chemoresistance in NHL, through the negative regulation of YY1 and KLF4. That also support the evidence that YY1 and KLF4 can be a potential therapeutic target in NHL.